Separately Fσ-measurable functions are close to functions of the first baire class - Banakh, T. O.; Vovk, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove that a Borel separately Fσ-measurable function f: X × Y → R on the product of Polish spaces is a function of the first Baire class on the complement X × Y M of a certain projectively meager set M ⊂ X × Y.